2005
DOI: 10.1128/aac.49.11.4649-4657.2005
|View full text |Cite
|
Sign up to set email alerts
|

A Class of Pantothenic Acid Analogs Inhibits Plasmodium falciparum Pantothenate Kinase and Represses the Proliferation of Malaria Parasites

Abstract: The growth and proliferation of the human malaria parasite Plasmodium falciparum are dependent on the parasite's ability to obtain essential nutrients. One nutrient for which the parasite has an absolute requirement is the water-soluble vitamin pantothenic acid (vitamin B 5 ). In this study, a series of pantothenic acid analogs which retain the 2,4-dihydroxy-3,3-dimethylbutyramide core of pantothenic acid but deviate in structure from one another and from pantothenic acid in the nature of the substituent attac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(65 citation statements)
references
References 23 publications
2
62
0
1
Order By: Relevance
“…Pantothenol is a competitive inhibitor of the phosphorylation of pantothenate by PfPanK (3). Recently, additional pantothenate analogs have been synthesized and shown to inhibit P. falciparum proliferation at concentrations severalfold lower than those required to inhibit the proliferation of a human cell line (17). Like pantothenol, these compounds inhibit parasite proliferation via a mechanism that entails competition with pantothenate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pantothenol is a competitive inhibitor of the phosphorylation of pantothenate by PfPanK (3). Recently, additional pantothenate analogs have been synthesized and shown to inhibit P. falciparum proliferation at concentrations severalfold lower than those required to inhibit the proliferation of a human cell line (17). Like pantothenol, these compounds inhibit parasite proliferation via a mechanism that entails competition with pantothenate.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibitors of the conversion of pantothenate to CoA are being investigated both as antimalarial (3,(15)(16)(17) and antibacterial (12)(13)(14) agents. Pantothenol, a pantothenate analog and a common ingredient of multivitamin supplements, shampoos, and cosmetics, is one such candidate that has been shown recently to inhibit P. falciparum growth in vitro and to inhibit the in vivo proliferation of the mouse parasite Plasmodium vinckei vinckei.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2) was synthesized using a published protocol (22,23). Details of the synthesis and analytical data are given in supplemental Fig.…”
Section: Methodsmentioning
confidence: 99%
“…For example, the provitamin pantothenol as well as a range of other pantothenate analogues have been shown to repress the proliferation of the malarial parasite Plasmodium falciparum. [11][12][13][14][15] A synthetic route for accessing geminal dialkyl-substituted pantothenamide derivatives was recently reported by some of us. 16 In this study, several compounds were synthesized and evaluated for antibacterial properties which revealed that larger substituents were not well tolerated at the gem-dimethyl position.…”
mentioning
confidence: 99%